Structuring the skies: Diel dynamics of migratory animal movement in the lower atmosphere - Silvia Giuntini; Carolyn S. Burt; Annika L. Abbott; Carrie Ann Adams; Maria Carolina T. D. Belotti; Yuting Deng; Miguel F. Jimenez; Jeffrey F. Kelly; Subhransu Maji; Meredith Nash‐Martin; Sam Simon; Daniel Sheldon; et al. (Ecology, 2025)
Earth's lower atmosphere is a vital ecological habitat, home to trillions of organisms that live, forage, and migrate through this medium. Despite its importance, this space is seldom considered a primary habitat for ecological or conservation prioritization, making it one of the least studied environments. However, it plays a crucial role as a global conduit for the transfer of biomass, weather, and inorganic materials. Fundamental research is essential to address core ecological questions related to the ecological consequences of this habitat's intricate spatial and temporal structure. To advance our understanding of airspace use by migratory animals, we analyzed over 108 million 5‐min radar observations from 143 NEXRAD sites, focusing on 24‐h diel cycles across the contiguous United States. This extensive dataset, spanning from 1995 to 2022, allowed us to quantify aerial space use by systematically identifying peak activity times, the portion of the airspace that contained the majority of migration activity, and the percentage of migrants passing across diurnal and nocturnal diel cycles. We found that airspace is used predominantly during nocturnal periods in both spring and autumn (88%), while summer exhibited a more balanced distribution (54% nocturnal). Additionally, the percentage of nocturnal activity increased with latitude in spring and autumn but decreased in summer. Peak aerial activity typically occurred about 4 h after local sunset in both spring and autumn, with variations based on latitude and longitude. During these peak times, on average, half of the aerial movement was confined within a vertical band of 516 meters, starting around 355 m above ground level. Our research underscores the need to view the lower atmosphere as a structured habitat with significant ecological importance.

The influence of multidecadal climate variability and abrupt landscape change on terrestrial ecosystem composition and fire regime in the upper Columbia River basin - A high-resolution Holocene perspective - Sam Mark; Cathy Whitlock; Mark Abbott; Byron Steinman; Alejandro Fernandez; Jennifer Steeple (Quaternary Science Reviews, 2024)

The association of COVID-19 incidence with temperature, humidity, and UV radiation – A global multi-city analysis - Luise Nottmeyer; Ben Armstrong; Rachel Lowe; Sam Abbott; Sophie Meakin; Kathleen M. O'Reilly; Rosa von Borries; Rochelle Schneider; Dominic Royé; Masahiro Hashizume; Mathilde Pascal; Aurelio Tobias; et al. (Science of The Total Environment, 2023)

Arctic concentration–discharge relationships for dissolved organic carbon and nitrate vary with landscape and season - Arial J. Shogren; Jay P. Zarnetske; Benjamin W. Abbott; Frances Iannucci; Alexander Medvedeff; Sam Cairns; Megan J. Duda; William B. Bowden (Limnology and Oceanography, 2021)
Climate change is intensifying the Arctic hydrologic cycle, potentially accelerating the release of carbon and nutrients from permafrost landscapes to rivers. However, there are limited riverine flow and solute data of adequate frequency and duration to test how seasonality and catchment landscape characteristics influence production and transport of carbon and nutrients in Arctic river networks. We measured high frequency hydrochemical dynamics at the outlets of three headwater catchments in Arctic Alaska over 3 years. The catchments represent common Arctic landscapes: low‐gradient tundra, low‐gradient and lake‐influenced tundra, and high‐gradient alpine tundra. Using in‐situ spectrophotometers, we measured dissolved organic carbon (DOC) and nitrate (NO 3 − ) concentrations at 15‐min intervals through the flow seasons of 2017, 2018, and 2019. These high‐frequency data allowed us to quantify concentration–discharge (C‐Q) responses during individual storm events across the flow season. Differences in C‐Q responses among catchments indicated strong landscape and seasonal controls on lateral DOC and NO 3 − flux. For the two low‐gradient tundra catchments, we observed consistent DOC enrichment (transport‐limitation) and NO 3 − dilution (source‐limitation) during flow events. Conversely, we found consistent NO 3 − enrichment and DOC dilution in the high‐gradient alpine catchment. Our analysis revealed how high flow events may contribute disproportionately to downstream export in these Arctic streams. Because the duration of the flow season is expected to lengthen and the intensity of Arctic storms are expected to increase, understanding how discharge and solute concentration are coupled is crucial to understanding carbon and nutrient dynamics in rapidly changing permafrost ecosystems.

Candidate gene database and transcript map for peach, a model species for fruit trees - Renate Horn; Anne-Claire Lecouls; Ann Callahan; Abhaya Dandekar; Lilibeth Garay; Per McCord; Werner Howad; Helen Chan; Ignazio Verde; Doreen Main; Sook Jung; Laura Georgi; et al. (Theoretical and Applied Genetics, 2005)

The path integral for dendritic trees - L. F. Abbott; E. Farhi; Sam Gutmann (Biological Cybernetics, 1991)